COVID-19 Impacts on Reproductive Ability, Childbearing, and Sexual Health- Psychological well-being in the Human Population; a Narrative Review - Ejehi, Mohammad Amin; Talebi, Marjan; Bozorgchami, Negar; Almasi Ghale, Roozbeh; Pouresmaeili, Farkhondeh (Archives of Men’s Health, 2024)
The coronavirus was the causative agent of a global epidemic from 2019 to 2022. The viral effect on sexual health and hormonal profile plus the rate of healthy births are important issues in general health. In this review, we studied the effect of coronavirus on reproductive health using more than 70 articles to understand the interaction of the virus with the reproductive system. High temperatures due to fever elevated ACE2 expression in both testis germ and somatic cells. Furthermore, they exhibit significantly elevated luteinizing hormone (LH) levels, but decreased testosterone, LH, and follicle-stimulating hormone (FSH)/LH ratios, which may indicate the possibility of hypogonadism and/or infertility. In contrast, women diagnosed with SARS-CoV infections during the first trimester of pregnancy are at a higher risk of spontaneous miscarriages, while infections occurring during pregnancy are more likely to result in preterm delivery. The Coronavirus can theoretically and potentially affect men’s fertility and sexual development, and possibly cause miscarriage in the first trimester of pregnancy with an unknown mechanism. The findings cannot affirm whether the hormonal alterations are due to a direct/indirect effect of the virus. Therefore, more studies are needed to answer related questions.